2018
DOI: 10.1186/s12902-018-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the joint effect of obesity and diabetes on functional disability at 3-months and on all-cause mortality at 1-year following an ischemic stroke

Abstract: BackgroundObesity and diabetes mellitus, or diabetes, are independently associated with post-ischemic stroke outcomes (e.g., functional disability and all-cause mortality). Although obesity and diabetes are also associated with post-ischemic stroke outcomes, the joint effect of obesity and diabetes on these post-ischemic stroke outcomes has not been explored previously. The purpose of the current study was to explore whether the effect of obesity on post-ischemic stroke outcomes differed by diabetes status in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Of the remaining 196 articles assessed for eligibility, 163 articles were excluded for having the same study population ( n = 5); for having a sample size < 100 ( n = 3); for lack of data on obesity, overweight, or underweight ( n = 108); or for not investigating the concerned outcome of stroke ( n = 47). Finally, 33 articles including 84,660 patients were included in the full analysis [9–41]. The detailed process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 196 articles assessed for eligibility, 163 articles were excluded for having the same study population ( n = 5); for having a sample size < 100 ( n = 3); for lack of data on obesity, overweight, or underweight ( n = 108); or for not investigating the concerned outcome of stroke ( n = 47). Finally, 33 articles including 84,660 patients were included in the full analysis [9–41]. The detailed process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of underweight/normal weight, n = 1) [15,31,33]. Most of the studies did not report a significant result.…”
Section: Outcome Of Patients With Ais Treated With Intravenous Thrombolysismentioning
confidence: 99%
See 1 more Smart Citation
“…44 This highlights the need for comprehensive and tailored management of patients with diabetes during the pandemic and beyond, 43 as well as in stroke patients with pre-existing diabetes who are at risk of poor outcomes after AIS. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]…”
Section: Discussionmentioning
confidence: 99%
“…The population of interest for this work is ischemic stroke survivors. Previous work looking at all-cause mortality at 1 year in ischemic stroke patients [ 24 ] showed that there was insufficient evidence to determine that the effect of obesity differed by diabetes status. This study was limited because the study population included acute ischemic stroke patients with at least a moderate stroke severity who met study eligibility.…”
Section: Methodsmentioning
confidence: 99%